Prevention and Control of Zoonoses in China Under the New Situation: Challenges and Strategies - Qingyun Liu; Peiling Wu; Xiangru Wang; Shengbo Cao; Huanchun Chen (中国工程科学)
Over the past 20 years, several emerging zoonotic epidemics have spread across the word, causing significant threats to human health, economic and social development, and agricultural security. This study reviews the current prevention and control situation worldwide, including the continuous emergence of new zoonoses, resurgence of existing zoonoses, acceleration of the spread of zoonoses through global integration, and impact of the new world pattern on the global prevention and control of zoonoses. Moreover, the study summarizes China's major achievements in the effective prevention and control of new epizoonoses such as COVID-19, the effective control or elimination of common zoonoses such as schistosomiasis, the advances in scientific and technological innovation, and the support of policies and laws for the prevention and control of zoonoses. The prominent problems in the field of zoonotic disease prevention and control in China include (1) the frequent occurrence of new and old zoonotic diseases and increased risk of introduction of zoonotic diseases from abroad, leading to serious drug resistance; (2) weak innovation abilities in prevention and control technologies and products; (3) inadequate prevention and control at the source and an imperfect prevention and control mechanism at the grassroots level; and (4) limited channels of international exchange and cooperation. A scientific and technological innovation system in zoonotic disease prevention and control is proposed and covers eight research directions: aetiology and epidemiology, structural and functional analysis of pathogens, immunity mechanisms and pathogenesis, diagnostic reagents, new vaccines, new drugs, disease-resistant breeding, and integrated prevention and purification of diseases, aiming to enhance the scientific and technological strength of zoonose prevention and control in China. Furthermore, the prevention and control strategies of zoonotic diseases in China are proposed. A plan should be implemented for purifying and eradicating major zoonotic diseases such as rabies, brucellosis, bovine tuberculosis, and echinococcosis in animal populations, so as to gradually eliminate some existing diseases. Meanwhile, new and sudden zoonoses should be prevented by closely monitoring the epidemic dynamics, strengthening the technical reserves for prevention and control, and efficiently responding to sudden imported cases.